2019
DOI: 10.3390/microorganisms7100424
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Pathogens as Risk Factors of Cardiovascular Diseases, Diabetes, Rheumatoid Arthritis, Cancer, and Chronic Obstructive Pulmonary Disease—Is There Cause for Consideration?

Abstract: Cardiovascular diseases, chronic obstructive pulmonary diseases, diabetes, rheumatoid arthritis, and cancer are the most common noncommunicable diseases (NCDs). These NCDs share risk factors with periodontal disease (PD), a preventable risk factor linked to lifestyle. The discussion regarding the association between these chronic diseases is more complex. There is still a significant knowledge gap particularly of the causal relationship between PD and NCDs. In this paper, we present fundamental knowledge of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
138
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 121 publications
0
138
0
1
Order By: Relevance
“…As periodontal diseases and lung cancer share many common and well-established risk factors, including smoking, alcohol use, and diabetes, 35,37,38 properly adjusted hazard ratios are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As periodontal diseases and lung cancer share many common and well-established risk factors, including smoking, alcohol use, and diabetes, 35,37,38 properly adjusted hazard ratios are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…During the meetings, all the children/adolescents showed affection towards the operators responsible for the project, and gradually showed more and more interest and enthusiasm for all the topics and for the practical demonstrations of oral hygiene techniques. Therefore, they took home a clear message: that being able to improve oral health could have great systemic implications for the organism, for the prevention of pathologies, and therefore for the quality of life in individuals [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that MPO, during periodontal disease, mediates the immune response at the endothelial level through specific heat shock proteins which has been shown to be useful for stimulating the production of cross-reactive T cells [47][48][49][50][51][52]. In this regard, this process which sees MPO as a key modulator [53][54][55][56][57][58], has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production [55,[58][59][60][61][62][63] which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases [43,[64][65][66][67][68]. Moreover, the oral microbiota is a key factor in the protection against the colonization of extrinsic pathogens that could impact systemic health [68].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, this process which sees MPO as a key modulator [53][54][55][56][57][58], has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production [55,[58][59][60][61][62][63] which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases [43,[64][65][66][67][68]. Moreover, the oral microbiota is a key factor in the protection against the colonization of extrinsic pathogens that could impact systemic health [68]. However, the imbalance of the ecosystem together with high levels of MPO, which can be caused by a weak immune system, lead to a challenge for oral and systemic health [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation